The Chukchi region: Arctic ocean : tectonic and sedimentary evolution - Hegewald, Anne (2012)
The Arctic Ocean is an area of increasing interest for research. Variations in the sensitive polar ecosystem influence the environment of the global Earth system and climate change. Therefore, reviews of modern Arctic Ocean system thereby provide the basis to interpret the Arctic Ocean evolution through its past. However, the evolution of the Arctic Ocean, especially the Amerasian Basin, remains controversial and multiple oceanic rift models still exist. During the ARK-XXIII/3 expedition in the summer of 2008, the Alfred Wegener Institute could acquire the first seismic data set - consisting of seismic reflection lines as well as wide-angle reflection and refraction data - in the northern Chukchi region and on the southern Mendeleev Ridge. In addition, further data sets (logging information, additional seismic lines, gravity data) were available and used within this thesis. Summarising the results, we could date six sediment horizons in the research area, using the age control from the exploration wells. Furthermore, with the interpretation of the tectonic elements the ages of evolution of the northern Chukchi region and the southern Mendeleev Ridge were derived. In addition, a complex 3D gravity model of the research area was calculated. Hence, two tectonic models for the origin of the Chukchi Borderland and the Mendeleev Ridge were developed. Moreover, two already existing oceanic rift models for the opening of the Amerasian Basin were modified based on our results. On the other hand, we used prograding sediment horizons on the Chukchi Shelf to reconstruct the first relative sea level curve for the Chukchi region, beginning in the Late Eocene. This curve led to conclusions about the existence of gateways between the Arctic Ocean and the other global oceans. Therefore, we suggest an isolated Arctic Ocean from the Eocene/Oligocene boundary to the Early Miocene, and a higher relative sea level in the isolated Arctic basin than in the global oceans during this time.